Danton - Przybyszewska, Stanisława 1901-1935; Prodromidès, Jean 1927-; Przybyszewska, Stanisława 1901-1935; Przybyszewska, Stanisława 1901-1935 (The Criterion Collection, 2009)
Georges Danton, the popular revolutionary leader, returns to Paris at a time when the new Republic is in disarray. Robespierre and his allies have set up a monstrous dictatorship, beginning the infamous "Reign of Terror." Danton pleads with the people for an end to the bloodshed which violates the spirit of their revolution.